2001
DOI: 10.1038/ni723
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous gene expression in medullary thymic epithelial cells mirrors the peripheral self

Abstract: Expression of peripheral antigens in the thymus has been implicated in T cell tolerance and autoimmunity. Here we identified medullary thymic epithelial cells as being a unique cell type that expresses a diverse range of tissue-specific antigens. We found that this promiscuous gene expression was a cell-autonomous property of medullary epithelial cells and was maintained during the entire period of thymic T cell output. It may facilitate tolerance induction to self-antigens that would otherwise be temporally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
850
4
21

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 949 publications
(906 citation statements)
references
References 60 publications
31
850
4
21
Order By: Relevance
“…In recent years, however, it has been shown that it is expressed in the thymus, along with many other tissue-restricted antigens [3]. AIRE is necessary for the expression of most of these antigens, but the possibility of additional quantitative regulation by factors specific for each antigen needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, however, it has been shown that it is expressed in the thymus, along with many other tissue-restricted antigens [3]. AIRE is necessary for the expression of most of these antigens, but the possibility of additional quantitative regulation by factors specific for each antigen needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been clearly demonstrated that the expression of self-antigens, such as insulin, in the medullary thymic epithelial cells (mTECs) is an essential component for central tolerance [1][2][3][4]. Thymocytes entering the thymus after their development in the bone marrow require signals to survive and exit to the periphery to join the properly formed circulating T lymphocytes [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TECs are classically divided into two specialized functional subsets, cortical (cTECs) and medullary (mTECs). While cTECs are important at early stages of T-cell development and mediate positive selection, mTECs are critical at later stages governing negative selection and providing survival signals to mature single-positive (SP) thymocytes [6,8,9]. The generation of these two functionally competent TEC compartments is a prerequisite for normal thymopoiesis.…”
Section: Introductionmentioning
confidence: 99%